'Cannabis' ontologies I: Conceptual issues with Cannabis and cannabinoids terminology. (December 2020) - Riboulet-Zemouli, Kenzi
Objective: Identify a coherent nomenclature for Cannabis sativa L. derived products and their analogues. Design: Research undertaken in parallel to the three-year assessment of Cannabis derivatives by the World Health Organisation. The scope is limited to Cannabis products intended for human incorporation (internal and topical consumption). Primarily embedded in pharmacognosy, the study incorporates a wide range of scholarly and grey literature, folk knowledge, archives, pharmacopœias, international law, field pharmacy, clinical and herbal medicine data, under a philosophical scrutiny. Generic and Cannabis -specific nomenclatural frames are compared to determine the extent to which they coincide or conflict. Results: All lexica reviewed use weak, ambiguous, or inconsistent terms. There is insufficient scientific basis for terms and concepts related to Cannabis at all levels. No sound classification exists: current models conflict by adopting idiosyncratic, partial, outdated, or utilitarian schemes to arrange the extraordinarily numerous and diverse derivatives of the C. sativa plant. In law and policy, no clear or unequivocal boundary between herbal and non-herbal drugs, nor natural and synthetic cannabinoids was found; current nomenclatures need updates. In science, the botanical Cannabis lexicon overlooks parthenocarpy, and wide disagreement remains as to the taxonomy and systematics of the plant; chemical research should address differences in kinds between synthetic cannabinoids ; pharmacopœias include little information related to Cannabis, and disagree on broader classes of herbal medicines, virtually failing to embrace many known Cannabis medicines. Since existing products and compounds fail to be categorised in an evidence-based manner, confusions will likely increase as novel cannabinoid compounds, genetic and biotechnological modifications surge. Conclusions: The lack of clarity is comprehensive: for patients, physicians, and regulators. This study proposes an update of terms at several levels. It points at gaps in morphological descriptions in botany and pharmacognosy and a need for a metaphysical address of cannabinoids. Methods of obtention are identified as a common criterion to distinguish products; the way forward suggests a mutually exclusive nomenclatural pattern based on the smallest common denominator of obtention methods. In the context of a swelling number of Cannabis products being consumed (be it via medical prescription, adult-use, 'hemp' foodstuff and cosmetics, or other purposes), this study can assist research, contribute to transparent labelling of products, consumer safety and awareness, pharmacovigilance, medical standards of care, and an update of prevention and harm reduction approaches. It can also better inform regulatory policies surrounding C. sativa, its derivatives, and other cannabinoid-containing products.